Increasing Internet Marketing Skills of Pesantren Anwarul Huda Students with Search Engine Optimization Tools - Abbas, Muhammad Hasyim Ibnu; Priambodo, Magistyo Purboyo; Suwanan, Ahmad Fawaiq; Munir, Syahrul (CV. Inara, 2022)
In the modern era, pesantren is required to be an educational institution that is not only independent in religious academics but also independent in economy. There have started many pesantren that have profit-based business units. One of the pesantren that has several business units is Pondok Pesantren Anwarul Huda (PPAH) Malang City. PPAH has an independent business unit engaged in the creative industry, namely screen-printing merchandise which is the result of the LP2M Community Service team of Universitas Negeri Malang. However, there are still many shortcomings and obstacles experienced by partners, namely the PPAH digital screen-printing business called